STRENGTHENING PERSONALITY, WORK MOTIVATION, TEAMWORK, AND ORGANIZATIONAL CULTURE IN AN EFFORT TO INCREASE ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): Empirical Study on Madrasah Ibtidaiyah Teachers in South Tangerang Using Path Analysis and SITOREM Method - Mildan Arsdan Fidinillah; Soewarto Hardhienata; Sri Setyaningsih (JF Publisher, 2024)
Teacher effectiveness is vital for student development in madrasah ibtidaiyah (Islamic primary schools) in South Tangerang. However, their Organizational Citizenship Behavior (OCB), particularly in areas like altruism and civic virtue, has been found suboptimal, raising concerns about teacher engagement and performance. This highlights the need to explore factors influencing OCB in this context. This research aims to investigate the impact of teamwork on the OCB of madrasah ibtidaiyah teachers, with a particular focus on the mediating role of organizational culture. This study employed a quantitative research design, utilizing path analysis to examine the causal relationships between teamwork, organizational culture, and OCB. Data were collected from a sample of 1,310 madrasah teachers across 83 institutions in South Tangerang, with preliminary research conducted on 30 samples from five madrasahs. The analysis included a homogeneity test and the application of SITOREM analysis to identify key indicators influencing the variables under study. The findings revealed a positive and significant influence of teamwork on OCB, mediated by organizational culture. The calculated tvalue for the mediation influence test was 4.270, exceeding the t table value of 1.98 at a significance level of 0.05, indicating that organizational culture partially mediates the relationship between teamwork and OCB. This suggests that while organizational culture enhances the positive effects of teamwork, the influence of teamwork on OCB remains significant even in its absence. The results underscore the importance of fostering teamwork and a strong organizational culture to improve OCB among madrasah ibtidaiyah teachers.